Analisis Perlindungan Hukum Dalam Transaksi Transfer Melalui Aplikasi Dana - Andi Muhammad Aidil; Muh Arya Darmawan; Summa Summa (CV. ITTC INDONESIA, 2025)
The development of information technology in Indonesia has had a significant impact on the financial sector, one of which is through the use of digital wallet applications or e-wallets. The DANA application, which is popular in Indonesia, makes it easy for users to conduct financial transactions, including fund transfers between users. The use of the DANA application presents challenges related to legal protection for consumers, especially in terms of transaction security and dispute resolution. This study aims to analyze the legal protection provided to consumers in fund transfer transactions through the DANA application, as well as the policies implemented by DANA in protecting user rights. This study uses a qualitative approach with normative and empirical legal methods. The results of the study show that although existing legal regulations, such as the Consumer Protection Law and the Electronic Information and Transactions Law, provide sufficient legal basis, there are still challenges in the implementation of existing regulations and policies, especially related to handling user complaints and securing personal data